2008
DOI: 10.1001/jama.299.13.1547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rimonabant on Progression of Atherosclerosis in Patients With Abdominal Obesity and Coronary Artery Disease

Abstract: BESITY HAS REACHED EPIdemic proportions in many developed countries, particularly the United States, where 66% of the adult population is considered overweight and 34% are obese, defined as a body mass index greater than 30. 1,2 Epidemiologists predict that the epidemic of obesity and its public health consequences will continue to increase over the next several decades, affecting both the developed and developing worlds. 3,4 An abdominal pattern of fat distribution produces For editorial comment see p 1601.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
243
1
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 383 publications
(267 citation statements)
references
References 39 publications
10
243
1
13
Order By: Relevance
“…Second, several factors such as insulin resistance, adipokine levels, and inflammatory markers, which influence the development of obesity [2][3][4] , were not assessed. Third, as mentioned in the STRADIVARIUS trial 21) , an interventional study examining how weight loss influences the effects of statins on coronary atherosclerosis, be conducted in obese patients should. Finally, only a small number of patients were enrolled in this study, and larger multi-center studies are needed to confirm our findings.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Second, several factors such as insulin resistance, adipokine levels, and inflammatory markers, which influence the development of obesity [2][3][4] , were not assessed. Third, as mentioned in the STRADIVARIUS trial 21) , an interventional study examining how weight loss influences the effects of statins on coronary atherosclerosis, be conducted in obese patients should. Finally, only a small number of patients were enrolled in this study, and larger multi-center studies are needed to confirm our findings.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Other recently completed and ongoing trials employing IVUS endpoints to evaluate novel CVD therapies include the use of rimonabant in patients with CHD and abdominal obesity 73 and of rosiglitazone vs. glipizide in patients with type-2 diabetes and CHD (APPROACH study ClinicalTrials. gov identifier: NCT00116831).…”
Section: Intravascular Ultrasoundmentioning
confidence: 99%
“…Furthermore, rimonabant also attenuates multiple inflammatory markers [e.g., tumor necrosis factor- (TNF-), C-reactive protein, etc. ], plasma leptin and insulin levels, and increases plasma adiponectin in obese patients with metabolic syndrome and/or type 2 diabetes, thereby attenuating the development of cardiovascular risk factors associated with obesity/metabolic syndrome and diabetes [18][19][20][21][22][23][24]. On the basis of these studies, it was also suggested that rimonabant may have favourable effects in atherosclerosis.…”
Section: State Of the Artmentioning
confidence: 99%
“…With this in mind, the results of the recent STRADIVARIUS clinical trial examining the effect of 18 months of rimonabant treatment on coronary disease progression in subjects with abdominal obesity/metabolic syndrome yielded somewhat disappointing results [19]. Rimonabant had no significant effect on the primary endpoint of coronary disease progression (the percent atheroma volume), however, it decreased the normalized total atheroma volume, which was the secondary endpoint [19]. The favourable effects of rimonabant on body weight and hormonal/metabolic parameters were similar to those observed in previous largescale trials.…”
Section: State Of the Artmentioning
confidence: 99%